Green office building investment in Malaysia: a review - Isa, Mona (2013)
This paper discusses the significant factors contributing to rationalising green office building investment in Malaysia. It also discusses the roles of investors and their participation in such investment. This review, based on previous research studies, contributes to an extension of property investment theoretical underpinning in green office building. Green Office Building is considered a new investment option which could enhance return by implementing green characteristics, either in new building construction or retrofitting an existing building with the aim to achieve a better return: financially, socially and environmentally. This paper also focuses on the barriers that prevent investors in making investments in green office buildings.